Energetics of swimming in man - Rennie, D. W.; Pendergast, D. R.; Di Prampero, P. E. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
An analysis of swimming that quantitatively interrelates external mechanical power, over-all mechanical efficiency, total energy input, and the average velocity of progression has been hampered in the past by the absence of data on the over-all resistive forces (i.e., form drag plus skin friction plus wave resistance) the swimmer must overcome during actual swimming. We shall refer to these resistive forces collectively as "body drag," Db. With a knowledge of Db, a quantitative analysis of swimming can be made to evaluate individual differences in performance and predict the energy cost of swimming.